1983
DOI: 10.1007/bf00334815
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of transcriptional and translational errors at nonsense codons in the lacZ gene of Escherichia coli

Abstract: Nonsense alleles in the lacZ gene of E. coli do not completely eliminate enzyme activity as errors during protein synthesis allow some chains to be completed. The relative contributions of transcriptional and translational errors to this leakiness were investigated by two methods: the introduction of rho- alleles into extreme-polar mutants and the kinetics of beta-galactosidase induction. Virtually all the errors appeared to be transcriptional in the case of two extreme-polar and one non-polar mutation. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…Several studies have reported large fluctuations in the level of errors among different codons encoding the same protein (14,15,17,18), suggesting a different degree of susceptibility to errors along the coding sequence. In this view, evolutionary pressure that shapes codon usage could allow different genes to be prone to unequal error rates according to their cellular function (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported large fluctuations in the level of errors among different codons encoding the same protein (14,15,17,18), suggesting a different degree of susceptibility to errors along the coding sequence. In this view, evolutionary pressure that shapes codon usage could allow different genes to be prone to unequal error rates according to their cellular function (35).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo measurements of errors in gene expression in bacteria have been estimated to occur at a rate of 10 −4 to 10 −5 per nucleotide during transcription and ≈10 −3 to 10 −4 per codon during translation. These error rates are significantly higher than that attributed to the highfidelity replication process, where the frequency of errors is as low as 10 −8 to 10 −9 per nucleotide (8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Parameters that influence translational fidelity include genetic background, antibiotics, and epigenetic states. Typically, the fidelity of translation has been considered less stringent than that of transcription (19,(23)(24)(25).In an effort to examine the contribution of transcriptional and translational errors and SII's potential role in proofreading, we have designed a reporter system to detect misincorporation events mediated by RNA polymerase II at an artificial stop codon engineered into a plasmid introduced into yeast. Using yeast strains with a deletion or a disruption of the SII-encoding gene (DST1), we were unable to find evidence that this cleavage-activating factor participates in proofreading.…”
mentioning
confidence: 99%
“…Parameters that influence translational fidelity include genetic background, antibiotics, and epigenetic states. Typically, the fidelity of translation has been considered less stringent than that of transcription (19,(23)(24)(25).…”
mentioning
confidence: 99%